KEBIJAKAN PENGGUNAAN SANKSI PIDANA DALAM PERUNDANG--UNDANGAN HUKUM ADMINISTRASI UNDANGAN HUKUM ADMINISTRASIUNDANGAN HUKUM ADMINISTRASI UNDANGAN HUKUM ADMINISTRASI - Eman Sulaiman (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2014)
AbstractThe use of criminal sanctions as the main sanction has indicated the extent towhich the level of understanding of the legislators to the problem of "crime andpunishment". At least show that the limited understanding of the use of criminalsanctions also affect the determination of criminal sanctions in administrativelaw. "Errors" in the formulation of the implications for the difficulty andconfusion in the law enforcement, because there is a gap of two disciplines,namely the criminal law on the one hand and on the other hand administrativelaw, which has its own procedural law. This confusion will lead to ambiguity inthe resolution of cases of violation of administrative law contains criminalsanctions, whether enforcement will be carried out by law enforcement agencieswithin the criminal justice sisitem or whether officials of the state administrationin the sphere of administration? Such circumstances, of course, will lead to theexistence of legal uncertainty for the community.Kata Kunci: sanksi pidana, hukum pidana, hukum administrasi